The discourses of the Brazilian Homeschool Association (Práxis Educativa, 2020)
The Homeschooling movement, in Brazil, which proposes removing children from school, disregarding any relationship with it, praises neoconservative and neoliberal policies. Therefore, some questions arise: How do these policies combine if one is conservative, and the other propagates marketing discourses of modernization and quality in school education? What are the discourses that are built with this movement? Who talks and who does this one talk to? Where do these discourses come from? In a theoretical dialogue, especially with Foucault, Apple, Masschelen and Simons, the information from the website of the Brazilian Homeschool Association – ANED is analyzed. Educating children at home is not just a matter of freedom of choice, as homeschool denotes much more about the conceptions and subjectivations of the subjects of a neoliberal and neoconservative society.Keywords: Homeschooling. Education at home. Family.